2019
DOI: 10.4037/ajcc2019931
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Prolonged Intensive Care Unit Stay Among Patients With Sepsis-Induced Hypotension

Abstract: Background Sepsis risk stratification tools typically predict mortality, although stays in the intensive care unit (ICU) of 24 hours or longer may be more clinically relevant for emergency department disposition. Objective To explore predictors of ICU stay of 24 hours or longer among infected, hypotensive emergency department patients. Methods A secondary ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…Increased respiratory rate as a risk factor of respiratory failure identified in this study is simple and convenient to apply for clinicians in their practice. This result is consistent with previous studies [ 7 , 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…Increased respiratory rate as a risk factor of respiratory failure identified in this study is simple and convenient to apply for clinicians in their practice. This result is consistent with previous studies [ 7 , 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…Previous researches demonstrated that neutrophils were involved in the development of sepsis 42 . Previous work identified that deleterious accumulation of neutrophils in organs resulted in MODS 43 . Our data showed that LPS injection resulted in severe neutrophil infiltration in lung, liver, kidney, and heart tissues.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated that AE improved sepsis-induced lung injury in part by decreasing neutrophil content. Besides, deleterious accumulation of neutrophils within remote vital organs led to collateral tissue damage and ultimately multiple organ failure [38]. Hence, deleterious activation of neutrophils was a critical reason leading to host tissue injury and organ damage during sepsis.…”
Section: Discussionmentioning
confidence: 99%